Travel survey methods quality and future directions - Stopher, Peter R.; Stecher, Cheryl (Emerald, 2006)
This book is a new chapter in the continuing focus of the International Steering Committee for Travel Survey Conferences (ISCTSC) on maintaining and improving the quality of data collection in transport surveys. The papers extend discourse on broad topic areas that have been addressed by the ISCTSC in previous conferences, provide an update on travel survey initiatives currently under way in many countries, and offer a glimpse into the future in the form of changing contexts, new topics, new technologies, and new standards from around the world, with an emphasis on standards and future research directions. This book is not a conference proceedings, but was derived from papers that were a part of the 7th International Conference on Travel Survey Methods, held at Playa Herradura, Costa Rica, during August 2004. All of the chapters were reviewed by three referees and only those papers that achieved the highest ratings were selected for inclusion in this book. The conference covered both passenger and freight transport, and focused on surveys that collect information directly from individuals or organisations (that is, it excluded traffic counts or other observational data collection).Delegates attended from North, Central, and South America, Europe, Asia, Australasia and Africa, so there was a keen interest in examining applicability of standards and looking at needed future research in regions outside of the North American/Western European context. This content extends discourse on existing topics, provides an update on current travel survey initiatives, and reflects on the future of the discipline. This book is derived from papers that were a part of the 7th International Conference on Travel Survey Methods. Authors come from diverse backgrounds throughout the world.